2017
DOI: 10.3390/ijerph14101266
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Puberty Timing: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis examined the associations between obesity and puberty timing based on scientific evidence. Eight electronic databases were searched up to February 2017 for eligible studies, and two reviewers screened the articles and extracted the data independently. A total of 11 cohort studies with 4841 subjects met the inclusion criteria. Compared with the group of normal-weight girls, the obese group had more girls with menarche (RR: 1.87, 95% CI: 1.59–2.19, 2 studies). The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
185
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(203 citation statements)
references
References 46 publications
11
185
1
6
Order By: Relevance
“…This suggests that a similar nutrition-mediated steroid activation may function in regulating insulin output of mammals and warrants further investigation, particularly in the context of several human disorders with nutrition-associated phenotypes (e.g. obesity and anorexia nervosa) that also impact timing of sexual maturity (Kaplowitz, 2008;Stipp, 2011;Wagner et al, 2012;Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a similar nutrition-mediated steroid activation may function in regulating insulin output of mammals and warrants further investigation, particularly in the context of several human disorders with nutrition-associated phenotypes (e.g. obesity and anorexia nervosa) that also impact timing of sexual maturity (Kaplowitz, 2008;Stipp, 2011;Wagner et al, 2012;Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Growth and maturation are tightly coordinated processes that result in animals of similar, genetically determined and species-specific adult size. Advances in recent years have revealed remarkable similarities in the mechanisms that coordinate growth and developmental timing of maturation in evolutionarily distant species such as fly and human, with major roles for steroid hormones in maturation and insulin signalling in growth (Brogiolo et al, 2001;Rulifson et al, 2002;Colombani et al, 2005;Kaplowitz, 2008;Stipp, 2011;Wagner et al, 2012;Rewitz et al, 2013;Nässel and Vanden Broeck, 2016;Li et al, 2017). Growth and time to maturation universally depend on nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that underlie the association between earlier AAM and higher T2D/IGT risk are unclear. Rapid postnatal weight gain [46] and childhood obesity [47,48] may precede early menarche, but also early menarche may promote adulthood obesity [49], and consequently increase T2D risk [3,50,51]. Hence, adiposity may be considered as both a partial confounder and partial mediator.…”
Section: Discussionmentioning
confidence: 99%
“…In males, however, some studies have found that higher childhood BMI is associated with later puberty, 10 13 14 , while others have found associations similar to those observed in females 8 9 1517 . In a recent systematic review and meta-analysis of 11 cohort studies, pre-pubertal obesity among females was associated with earlier menarche but there was insufficient and inconsistent evidence in males 18 . A recent Mendelian randomisation (MR) analysis suggested that earlier age at menarche causes higher adult BMI but lacked data on pre-pubertal BMI for adjustment 19 .…”
Section: Introductionmentioning
confidence: 99%